2012
DOI: 10.1088/0029-5515/52/8/083007
|View full text |Cite
|
Sign up to set email alerts
|

Non-resonant magnetic braking on JET and TEXTOR

Abstract: The non-resonant magnetic braking effect induced by an Non-Axisymmetric Magnetic Perturbation (NAMP) is investigated on JET and TEX-TOR. The collionality dependence of the torque induced by the = 1 NAMP field is obtained on JET. The observed torque is located mainly in the plasma core (normalized < 0.4). It increases with decreasing collisionality. The calculation shows that it is close to the transition between the − √ and the superbanana plateau regimes in the plasma core. The NTV torque is modeled by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 49 publications
(128 reference statements)
11
47
0
Order By: Relevance
“…8, compensation of the n ¼ 3 error in NSTX increases the rotation and improves the stability to resistive wall modes at high beta. 15 JET experiments with n ¼ 1 perturbations have also shown good agreement with NTV predictions of braking, 80 account the calculated plasma response. In the case of an applied n ¼ 1 "error field" that is compensated by another n ¼ 1 coil set with a different geometry, non-resonant NTV braking by the uncompensated poloidal harmonics may decrease 63 or increase 63,81 depending on the geometry of the error field and compensation coils, and on the strength of the kink-resonant plasma response to the external fields.…”
Section: E Limitations Of Single-mode Modelssupporting
confidence: 64%
“…8, compensation of the n ¼ 3 error in NSTX increases the rotation and improves the stability to resistive wall modes at high beta. 15 JET experiments with n ¼ 1 perturbations have also shown good agreement with NTV predictions of braking, 80 account the calculated plasma response. In the case of an applied n ¼ 1 "error field" that is compensated by another n ¼ 1 coil set with a different geometry, non-resonant NTV braking by the uncompensated poloidal harmonics may decrease 63 or increase 63,81 depending on the geometry of the error field and compensation coils, and on the strength of the kink-resonant plasma response to the external fields.…”
Section: E Limitations Of Single-mode Modelssupporting
confidence: 64%
“…As shown in Figs. 5(f) and 5(g), the evaluated electron fluid perpendicular rotation, ω e⊥ , and E ×B one, ω E×B , near the pedestal top becomes very close to 0 after the application of RMPs because of rotation braking [30][31][32]. According to recent plasma response theories [11] and modelings [8,10,22], the resonant harmonics near the pedestal top, where ω e⊥ ≈ 0, may penetrate.…”
mentioning
confidence: 90%
“…The knowledge of various mechanisms and corresponding torques driving the toroidal plasma rotation is therefore crucial for operation control of these fusion experiments. Dedicated experimental studies at NSTX [1], DIII-D [2] and JET [3,4] have shown a strong dependence of the plasma rotation on non-axisymmetric magnetic perturbations (e.g., from coils for mitigation of edge localized modes (ELMs), from toroidal field (TF) coil ripple and from error fields). The observed changes in plasma rotation were in agreement with theoretical predictions for the torque produced by ‡ See http://www.euro-fusionscipub.org/mst1 non-resonant non-axisymmetric magnetic perturbations, which are based on analytical and semi-analytical approaches [5,6,7].…”
Section: Introductionmentioning
confidence: 99%